Spatial Distribution and Population Characteristics of Xylocarpus sp. in North Halmahera Regency North Maluku - A.R Tolangara; Nurul Amalia R.L; Abdu MasÃ¢â¬â¢ud; Sundari Sundari (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2022)
North Halmahera Regency is one of the mangrove spots of the Xylocarpus sp species with a fairly abundant amount. This study aims to determine the distribution map of Xylocarpus sp species and population character of Xylocarpus sp in North Halmahera Regency. This research was conducted from April to June 2021. The method used included a mapping survey of Xylocarpus sp by recording the coordinates from GPS for each Xylocarpus sp found. Determination of population character of Xylocarpus sp was done by observing plant morphology related to vitality and periodicity. Data analysis was carried out by processing coordinate data and observational data on the character of the population of Xylocarpus sp into a base map through a GIS application. The results showed that the species Xylocarpus sp. found in North Halmahera district was Xylocarpus granatum. The distribution pattern of Xylocarpus granatum in North Halmaera is spread in groups. Population characteristics show Xylocarpus granatum in very low sociality conditions, vitality in a well-growing state, periodicity in flowering and fruiting conditions.